SETS: Scalable and Efficient Tree Search in Dependency Graphs - Juhani Luotolahti; Jenna Kanerva; Sampo Pyysalo; Filip Ginter (United States, 2022)
We present a syntactic analysis query toolkit geared specifically towards massive dependency parsebanks and morphologically rich languages. The query language allows arbitrary tree queries, including negated branches, and is suitable for querying analyses with rich morphological annotation. Treebanks of over a million words can be comfortably queried on a low-end netbook, and a parsebank with over 100M words on a single consumer-grade server. We also introduce a web-based interface for interactive querying. All contributions are available under open licenses.
Proceedings of the 2015 Conference of the North American Chapter of the Association for Computational Linguistics: Demonstrations